Effect of radial grooves pads on copper chemical mechanical polishing. (15th November 2022) - Bae, Chulwoo; Oh, Shinil; Kim, Juhwan; Kwak, Donggeon; Oh, Seungjun; Kim, Taesung
Abstract: In this study, the effect of radial grooves (RG) pads employed in the copper chemical mechanical polishing/planarization (CMP) process was investigated, to improve the copper CMP performance. To this end, four types of pads were selected according to the number of RGs; the numbers of RGs were 0, 8, 16, and 32. The amount of slurry inflow/outflow was calculated for the selected number of RGs over the same duration, and the change in the slurry inflow/outflow according to the rotational speed of the head/platen was determined using a numerical method. The simulation results thus obtained demonstrated the differences in the amount of slurry inflow/outflow according to the number of RGs and the rotational speed of head/platen. At 90 rpm, the new slurry mass fractions of the circular groove (CG) pad and the RG-32 pad were 0.52754 and 0.67606, respectively, and the new slurry mass fraction of the RG-32 pad increased by about 22% compared to the result of the CG pad. Subsequently, the CMP process was performed using four types of pads at different head/platen rotational speed, and Cu removal rates were compared. According to the CMP evaluation results, the Cu removal rates improved with an increase in the number of RGs. At 90 rpm, the Cu wafer removal rates of the CG pad and the RG-32 pad were 4051.3 Å/min and 5047.2 Å/min, respectively, and when the RG-32 pad was used, the Cu wafer removal rate was increased by about 24.6%. Furthermore, the roughness of the Cu wafers was improved by increasing the number of RGs. Therefore, supplying new slurry and releasing the old slurry can affect the performance Cu CMP process.